The not-so-faraway adventure - Larsen, Andrew, 1960- (Kids Can Press, 2016)
"Theo's Poppa was an explorer. He had been everywhere. He kept an old trunk packed with the pictures, postcards, maps and menus that he had collected on his adventures. Someday, Theo wants to be an explorer, too. For now, it's Poppa's birthday, and Theo has planned a special trip to the beach with him to celebrate. They plot out their course on a map they've drawn and then take the streetcar to the local beach, where they stroll in the sand, hunt for stones and slurp gazpacho at the beachside restaurant. It's a perfect day, and Theo is so happy to have given Poppa just the right gift. But best of all, Theo has also had her first lesson in being an explorer: you don't have to travel far from home to have an adventure!"--